2015
DOI: 10.1063/1.4918329
|View full text |Cite
|
Sign up to set email alerts
|

Nanomotor dynamics in a chemically oscillating medium

Abstract: Synthetic nanomotors powered by chemical reactions have potential uses as cargo transport vehicles in both in vivo and in vitro applications. In many situations, motors will have to operate in out-of-equilibrium complex chemically reacting media, which supply fuel to the motors and remove the products they produce. Using molecular simulation and mean-field theory, this paper describes some of the new features that arise when a chemically powered nanomotor, operating through a diffusiophoretic mechanism, moves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…We show that, as previously reported [46], the effect of the introduction of catalytic obstacles in a system with a complex oscillating chemical reaction is to reduce the oscillations in it, leading the system to a fixed point where the limit cycles are shifted. Additionally, we fit these oscillations to a damped periodic function, finding that its decay constant γ scales linearly with the volume fraction occupied by the obstacles (φ) after a certain amount of obstacles is introduced; meaning that there exists a critical damping value for φ.…”
Section: Discussionsupporting
confidence: 79%
“…We show that, as previously reported [46], the effect of the introduction of catalytic obstacles in a system with a complex oscillating chemical reaction is to reduce the oscillations in it, leading the system to a fixed point where the limit cycles are shifted. Additionally, we fit these oscillations to a damped periodic function, finding that its decay constant γ scales linearly with the volume fraction occupied by the obstacles (φ) after a certain amount of obstacles is introduced; meaning that there exists a critical damping value for φ.…”
Section: Discussionsupporting
confidence: 79%
“…In an inert environment, the medium itself neither creates nor destroys the substrate required for the machines’ catalytic behavior. However, molecular dynamics simulations have shown that the chemical activity of the underlying environment may alter diffusiophoresis [25, 26]. Those simulations illustrate that background chemical activity can reduce the self-propulsion speed [25].…”
Section: Introductionmentioning
confidence: 99%
“…By periodically varying the chemical constraints cyclic expansion and contraction of the gel-like filament states was obtained, which are reminiscent of the similar states in oscillating hydrogels activated by the Belousov-Zhabotinsky reaction. If the fluid phase reactions that control the nonequilibrium state can sustain oscillations and couple to the motor reactions 43 , then autonomous control of the filament oscillations could also be achieved.…”
Section: Discussionmentioning
confidence: 99%